PENGARUH POTONGAN HARGA, DISTRIBUSI FISIK DAN PROMOSI PENJUALAN TERHADAP PENJUALAN - Resa Nurmala (Program Studi Ilmu Administrasi Bisnis FISIP UNPAS, 2020)
ABSTRACT Selamat Lestari Mandiri is a company engaged in the sale of motor vehicles and automobiles. Car with brand Toyota and motorcycle brand Honda. The problems faced were experiencing a decline in sales from September to November 2011. The problem is allegedly caused by the price cut in the form of a cash rebate given by PT. Selamat Lestari Mandiri is considered to be too low, physical distribution channel of the purchase or follows i.e. the number of products sent the main dealer does not correspond to the number of purchase requests submitted by PT Selamat Lestari Mandiri. Another cause of sales promotion of the promotion of salespeople in the monotonous sale contest, there is no change in its promotion.The purpose of this research is to know the implementation of discounted prices, the implementation of physical distribution, the implementation of sales promotions, sales execution and to know the magnitude of the influence of price cuts, physical distribution and sales promotion On the sale of Honda's motor products PT Selamat Lestari Mandiri Sukabumi. The research methods used are descriptive research methods and associative research methods. The technical collection of data is done by observation, interviews, questionnaire dissemination, literature study, and documents given by the company.Based on data obtained from the analysis results indicates that the correlation analysis of product-moment is generated By 0.665 means that all three influences are strong in influencing the sale, the coefficient of determination 42.2% and 57.8% are caused by other variables not examined in this study. The result of calculating the F hypothesis test count is greater than the F table (10.847 > 2.833.) so that H0 is rejected and H1 is received. That is, there is a significant influence between rebate, physical distribution, and sales promotion to sales.